On the uniqueness of the limit amplitude for the induced vibrations in strati (2011)
For three-dimensional exponentially stratied ows we make a review of our previous results and present a new corollary which consist of a detailed analysis for the classes of uniqueness of the solutions of the relevant equation for the limit amplitude of the induced vibrations caused by a periodic external force. Our main result is that for a frequency outside of the spectrum the limit amplitude is unique, while for a frequency belonging to the spectrum the limit amplitude loses the uniqueness.